Kinetics of the reactions of OH with CO, NO, and NO2 and of HO2 with NO2 in air at 1 atm pressure, room temperature, and tropospheric water vapour concentrations - M. Rolletter; A. Hofzumahaus; A. Novelli; A. Wahner; H. Fuchs; H. Fuchs (Atmospheric Chemistry and Physics)
The termolecular reactions of hydroxyl radicals (OH) with carbon monoxide (CO), nitric oxide (NO), and nitrogen dioxides (NO2) and the termolecular reaction of hydroperoxy radicals (HO2) with NO2 greatly impact the atmospheric oxidation efficiency. Few studies have directly measured the pressure-dependent rate coefficients in air at 1 atm pressure and water vapour as third-body collision partners. In this work, rate coefficients were measured with a high accuracy (<5 %) at 1 atm pressure, at room temperature, and in humidified air using laser flash photolysis and detection of the radical decay by laser-induced fluorescence. The rate coefficients derived in dry air are (2.39±0.11)×10-13<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="101pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="11f110e34de386442d86daf5914f1b5b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-3481-2025-ie00001.svg" width="101pt" height="15pt" src="acp-25-3481-2025-ie00001.png"/></svg:svg> cm3 s−1 for the OH reaction with CO, (7.3±0.4)×10-12<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="89pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="2e227973210dd155e6f3bacf2f3a22c9"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-3481-2025-ie00002.svg" width="89pt" height="15pt" src="acp-25-3481-2025-ie00002.png"/></svg:svg> cm3 s−1 for the OH reaction with NO, (1.23±0.04)×10-11<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="101pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="d06c4a90661d2a63280fe6e6cf460bfc"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-3481-2025-ie00003.svg" width="101pt" height="15pt" src="acp-25-3481-2025-ie00003.png"/></svg:svg> cm3 s−1 for the OH reaction with NO2, and (1.56±0.05)×10-12<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="101pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="d68884290d6df8929a89c1c9b34a263e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-3481-2025-ie00004.svg" width="101pt" height="15pt" src="acp-25-3481-2025-ie00004.png"/></svg:svg> cm3 s−1 for the HO2 reaction with NO2. For the OH reactions with CO and NO, no dependence on water vapour was observed for the range of water partial pressures tested (3 to 22 hPa), and for NO2, only a weak increase of 3 % was measured, in agreement with the study by Amedro et al. (2020). For the rate coefficient of HO2 with NO2 an enhancement of up to 25 % was observed. This can be explained by a faster rate coefficient of the reaction of the HO2–water complex with NO2 having a value of (3.4±1.1)×10-12<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="89pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="618717defd8aa3503efae22097db1c11"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-3481-2025-ie00005.svg" width="89pt" height="15pt" src="acp-25-3481-2025-ie00005.png"/></svg:svg> cm3 s−1.